Класифікація часових рядів на основі візуалізації графів видимості - Рижанов, В. С. (ХНУРЕ, 2021)
The classification process can solve many problems in different areas. This article describes methods for obtaining an image based on a time series. The main idea is to classify the time series in its other form
Keywords: часовий ряд; класифікація часових рядів; граф видимості; нейронна мекрежа